IC 9099 Surface Subsidence Over Longwall Panels In The Western United States - Monitoring Program And Final Results At The Price River Coal Co. No. 3 Mine, Utah - Alan J. Fejes (The National Institute for Occupational Safety and Health (NIOSH), 1986)
As part of its mine subsidence research program, the Bureau of Mines and the American Electric Power Co. cooperated on a study, conducted at the Price River Coal Co. No. 3 Mine, directed toward developing the capability to estimate the surface subsidence resulting from longwall mining in a geologic, topographic, and mining environment common to coalfields in the Western United States. Subsidence was monitored at the No. 3 Mine over two adjacent longwall panels. The subsidence study area was reduced when the two planned panels were reduced in length because of equipment failure and a mine fire. Subsidence was measured for 21 months. Subsidence continued for 6 months after mining had been completed. A maximum of 2.2 ft of subsidence occurred over the two longwall panels mined at an overburden depth ranging from 300 to 1,500 ft.